Baicalin prevents pulmonary arterial remodeling in vivo via the AKT/ERK/NF‐κB signaling pathways. (1st November 2019) - Yan, Guosen; Wang, Jinxia; Yi, Tao; Cheng, Junfen; Guo, Haixu; He, Yuan; Shui, Xiaorong; Wu, Zeyong; Huang, Shian; Lei, Wei
Abstract : Pulmonary arterial hypertension is a rapidly progressive and often fatal disease. As the pathogenesis of pulmonary arterial hypertension remains unclear, there is currently no good drug for pulmonary arterial hypertension and new therapy is desperately needed. This study investigated the effects and mechanism of baicalin on vascular remodeling in rats with pulmonary arterial hypertension. A rat pulmonary arterial hypertension model was constructed using intraperitoneal injection of monocrotaline, and different doses of baicalin were used to treat these rats. The mean pulmonary arterial pressure (mPAP) and right ventricular systolic pressure (RVSP) were measured with a right heart catheter. Moreover, the hearts were dissected to determine the right ventricular hypertrophy index (RVHI). The lung tissues were stained with H&E and Masson's staining to estimate the pulmonary vascular remodeling and collagen fibrosis, and the expression of proteins in the AKT, ERK, and NF‐κB p65 phosphorylation (p‐AKT, p‐ERK, p‐p65) was examined by Western blot analysis. We found that compared with untreated pulmonary arterial hypertension rats, baicalin ameliorated pulmonary vascular remodeling and cardiorespiratory injury, inhibited p‐p65 and p‐ERK expression, and promoted p‐AKT and p‐eNOS expression. In conclusion, baicalin interfered with pulmonary vascular remodeling and pulmonary arterial hypertension development in rats through the AKT/eNOS, ERK and NF‐κB signaling pathways.